Influences of behaviour and physiology on body mass gain in the woylie (Bettongia penicillata ogilbyi) post-translocation - Page, K.D.; Ruykys, L.; Miller, D.W.; Adams, P.J.; Bateman, Bill; Fleming, P.A. (CSIRO PUBLISHING, 2019)
Context: Temperament can affect an individual's fitness and survival if it also influences behaviours associated with predator avoidance, interactions with conspecifics, refuge selection and/or foraging. Furthermore, temperament can determine an individual's response to novel stimuli and environmental challenges, such as those experienced through translocation. Increasing our understanding of the effect of temperament on post-translocation fitness is thus necessary for improving translocation outcomes. Aims: The aim was to test whether differences in an individual's behaviour or physiology could help predict body mass changes post-translocation in the woylie (brush-tailed bettong, Bettongia penicillata ogilbyi). In the absence of predation (due to release into a predator-free exclosure), body mass was used as a proxy for an individual's success in securing resources in the new habitat, and therefore fitness. Methods: Forty woylies were translocated from two predator-free exclosures to a larger exclosure, all in Western Australia. Behavioural and physiological measures were recorded during trapping, processing, holding, and release, and again at re-capture ∼100 days post-release. Key results: Translocated woylies generally increased in body mass post-translocation. This suggests that, in the absence of predation, the selected candidates were able to cope with the stress of translocation and possessed the behavioural plasticity to successfully find resources and adapt to a novel environment. The strongest predictors of body mass gain were sex, heart rate lability and escape behaviour when released (a convoluted escape path). Conclusions: There was no significant difference in body mass between males and females pre-translocation but females showed greater mass gain post-translocation than did males, which could reflect greater investment in reproduction (all females had pouch young). Heart rate lability and escape behaviour are likely to reflect reactivity or fearfulness, a significant temperament trait in the context of translocation success. Implications: Behavioural measures that can be easily incorporated into the translocation process-without increasing stress or affecting welfare of individuals-may hold promise for predicting the fate of translocated animals.